The Challenges of Arabic Language Learning in the 13th Batch of the BBA (Belajar Bahasa Arab) Program - Hanifah , Amalia; Hussin, Mohamad; Mukhlis, Abdul; Yoyo, Yoyo (Journal of Arabic Language Studies and Teaching, 2025)
Language plays an essential role in global communication, with Arabic holding a prominent status alongside English due to its literary richness and its significance within the Muslim community. In Indonesia, Arabic language education is widely available, exemplified by the BBA (Belajar Bahasa Arab) program, which offers online instruction. This study explores the learning challenges encountered by tutors and participants in the program’s 13th cohort. Employing a qualitative descriptive approach, data were gathered through interviews with one tutor and nine participants, supported by observation and phenomenological analysis. The results identify two primary categories of challenges: linguistic and non-linguistic. Linguistic challenges pertain to participants’ limited mastery of fundamental Arabic linguistic features, while non-linguistic challenges involve technical issues such as unstable internet connections and low learning motivation. These findings underscore the need for enhanced pedagogical strategies and improved technological infrastructure to increase the effectiveness of online Arabic language instruction.